REDD+ as performance-based aid: General lessons and bilateral agreements of Norway - Arild Angelsen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
REDD+, when it officially became part of the international climate agenda in 2007, was an idea about payment to countries and projects for reducing emission from forests, with funding primarily from carbon markets. REDD+ has since become multi-objective; the policy focus has changed from payments for environmental services (PES) to broader policies, and international funding is mainly coming from development aid budgets. This aidification of REDD+ has made it similar to previous efforts of conditional, result-based, or performance-based aid (PBA). But, experience of PBA, in other sectors, has hardly been brought into the REDD+ debate. A major conclusion from earlier research is that aid cannot buy policy reforms, yet this remains a major idea in current REDD+ discourses. This paper reviews the main challenges in designing and implementing a system of PBA in terms of donor spending pressure, performance criteria, benchmark setting, risk sharing, and credibility, in terms of amount of funding provided. It then reviews four bilateral REDD+ agreements Norway has entered with Tanzania, Brazil, Guyana, and Indonesia. Some elements of performance-based payments were included, and these agreements and the aid experience provide valuable lessons for design and implementation of future REDD+ mechanism.
Keywords: O13; Q23; Q54; 330; deforestation; climate change; conditionality; PES; Norway